Token Economy to Improve Concentration among Students with Learning Disabilities in Primary School - Noor Azreena A Aziz; Mohd Hanafi Mohd Yasin (Department of Special Education, 2018)
This study aimed to increase student’s concentration on learning and facilitating process in the classroom. A student from the Special Education Integration Program. was selected as the respondent of this study. The token economy approach had been implemented in this study to solve respondent behavioural problem who was not paying attention when completing classroom task. This study employed a qualitative, A-B-A single subject design which A and B represented baseline and intervention phase respectively. Observation was carried out in three different phase, namely baseline (2 weeks), intervention (2 weeks) and no intervention (2 weeks). Total duration of this study was 6 weeks. During early observation, to be found that interruption from other classes had caused distraction to respondent in completing the task given. Therefore, token economy was used to enhance students’ motivation in paying attention and completing the task correctly. Token is given when respondent managed to answer questions correctly and neatly, and did not exhibit any disruptive behaviour within the stipulated period. Then, token was redeemed for tangible reinforcement according to the total scores of token. The results indicate that respondent had succesfully paying attention during completion of task.